A Consideration of Kafka’s Metamorphosis as a Metaphor for Existential Anxiety (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
This paper considers Franz Kafka's Metamorphosis in light of a dichotomy between age as a font of wisdom and experience, and, conversely, as a gruesome fate for those that survive youth. It is inspired by my counselling work with disability and infirmity.
Keywords: Age; metamorphosis; death; time; youth; old